A Comparative Study of Two Modalities in Pain Management of Patients Presenting with Chronic Brachial Neuralgia - Razak, Izzati; Chung, Tze Yang; Ahmad, Tunku Sara (Mary Ann Liebert, 2019)
Objectives: The study aims to assess, evaluate, and compare the efficacy of acupressure and hypnotherapy in the management of pain in patients presenting with chronic brachial neuralgia (CBN). Design: Randomized controlled trial. Settings/location: Department of Orthopaedic Surgery, University Malaya Medical Centre, Kuala Lumpur, Malaysia. Subjects: Forty patients with CBN following traumatic brachial plexus injury from 2012 to 2017. Intervention: Therapy for a duration of 1 month in two groups; subjects in the hypnotherapy group received a weekly session of clinical hypnotherapy (total of four times) using a standardized protocol, while subjects in the acupressure group were guided by an acupuncturist during the initial session, received 2 month take home supply of acupressure patches, and were reviewed fortnightly. Outcome measures: The Visual Analog Scale, the Brief Pain Inventory, and the SF-36v2® Health Survey were recorded at different time points; 1 month pretreatment (week 0), pretreatment (week 4), post-Treatment (week 8), and 4 months post-Treatment (week 20). Results: There was a statistically significant improvement in the average pain intensity from pretreatment to post-Treatment score in both groups. The pain intensity increased 4 months later; however, the pain intensity was still significantly reduced in comparison with pretreatment scores. The study suggests that both treatment outcomes are effective in terms of alleviating pain and improving quality of life in subjects with CBN, to a different degree. Conclusion: Overall, both therapies were able to improve the pain intensity and quality of life significantly during the treatment period. Hypnotherapy was observed to have a better carryover effect compared to acupressure, especially in terms of improving quality of life and the mental component score. © Copyright 2019, Mary Ann Liebert, Inc., publishers 2019.